Potency of coffee by-products as sustainable added material in bio/edible film development - Wardana, Ata Aditya; Febrianto, Noor Ariefandie; Marcellino, Vincensius; Wigati, Laras Putri; Nkede, Francis Ngwane; Tanaka, Fumina; Tanaka, Fumihiko (Frontiers in Sustainable Food Systems, 2025)
Coffee processing generates abundant by-products including husk, pulp, spent coffee grounds, and silver skin, which pose environmental challenges but potential as functional materials. This paper highlights recent advancements in the development of sustainable films enriched with coffee by-products for food packaging applications. Rich in lignocellulosic fibers, polyphenols, and antioxidants, by-products could be transformed into film-forming matrices, fillers, or bioactive additives to improve the bio/edible film performances. Tensile strength, elasticity, and thermal stability were improved through fiber and lignin content of coffee by-product inclusion. Their incorporation also improved barrier performance, reducing water vapor and gas permeability and enhancing ultraviolet (UV) resistance, thus extending food shelf life. Additionally, rich in biofunctional compounds such as caffeine and chlorogenic acid, these by-products significantly boost the films antioxidant and antimicrobial activities, offering protection against oxidative spoilage and microbial contamination. The challenges remained regarding material standardization, sensory impact, and large-scale application.